THE MAIN POINTS IN DIRECT TRANSLATION OF POETRY (Proceedings of International Educators Conference, 2023)
This article deals with issues of main points as content, rhyme, rhythm, structure and others in direct translation of poetry. In the first part of the article, scientific approaches and definitions of famous scholars concerning the translation methods of poetry highlighted, and the second part includes analysis on correspondence of content and rhyme in direct poetry translation.